Preparation and characterization of Sb-doped SnO2 (ATO) nanoparticles with NIR shielding by an oxidation coprecipitation hydrothermal method. Issue 11 (1st September 2020) - Li, Meng; Cai, Zi; Yang, Yun; Wang, Yuanhao; Zhong, Hong; Li, Tao
Abstract: ATO nanoparticles with different doping amounts of antimony were synthesized by an oxidation coprecipitation hydrothermal method. The obtained ATO nanoparticles were characterized by XRD, FTIR, HRTEM, EDS, XPS and UV-Vis-NIR Spectroscopy. The results show that ATO nanoparticles have been successfully prepared. The transmittance spectra of the sample films coated on the glasses in IR band wavelength demonstrates excellent NIR shielding performance, which means prepared ATO films could be used as thermal insulating coating on the surface of building glass. GRAPHICAL ABSTRACT: